2013
DOI: 10.1111/apa.12339
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal systemic inflammatory responses of growth-restricted preterm newborns

Abstract: AIM To compare the early postnatal pattern of systemic inflammation in growth-restricted infants born before the 28th week of gestation to that of appropriately grown peers. METHODS We measured the concentrations of 25 inflammation-related proteins in blood spots collected from 939 newborns during the first 2 postnatal weeks. We calculated the odds ratios (99% confidence intervals) that concentrations would be in the highest quartile. RESULTS Severely growth-restricted infants (birth weight Z-score < -2) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
85
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 22 publications
2
85
0
5
Order By: Relevance
“…Previous studies also revealed an association between inflammation and fetal growth restriction [19,20]. Increased serum inflammatory markers were detected in growth restricted infants on postnatal day 14 [21]. Furthermore, Hill et al found higher concentrations of renin and lower concentrations of leptin in neonates with IUGR accompanied by antenatal abnormal umbilical artery Doppler waveforms [unpublished raw data].…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies also revealed an association between inflammation and fetal growth restriction [19,20]. Increased serum inflammatory markers were detected in growth restricted infants on postnatal day 14 [21]. Furthermore, Hill et al found higher concentrations of renin and lower concentrations of leptin in neonates with IUGR accompanied by antenatal abnormal umbilical artery Doppler waveforms [unpublished raw data].…”
Section: Discussionmentioning
confidence: 96%
“…Higher rates of significant patent ductus arteriosus within 48 hours of birth have been observed among growth-restricted preterm infants of 26–32 weeks in comparison to non-growth-restricted infants (65% vs 40%) [11]. In addition, growth restricted infants have higher concentrations of some inflammation-related proteins, which might affect their response to pharmacologic PDA treatment [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation is recognized as another risk factor for CLD and a recent report demonstrates that growth-restricted preterm newborns are at increased risk for postnatal elevated concentrations of inflammation-associated proteins [19]. Fetal growth restriction impact on lung development and postnatal systemic inflammation might be two synergistic factors leading to the risk of CLD.…”
Section: Discussionmentioning
confidence: 99%